Screening of N-Acyl Homoserine Lactone-degrading Bacteria and Evaluation of Their Quorum Quenching Activities - Xiqian TAN; Xiaoqing WANG; Fangchao CUI; Dangfeng WANG; Xinran LÜ; Xuepeng LI; Jianrong LI (Shipin gongye ke-ji)
To study the types of quorum quenching bacteria in soil and their quorum quenching characteristics, the study screened, isolated, and identified quorum quenching strains from soil and assessed their quorum quenching properties, the inhibitory and dispersion abilities on the biofilm of Hafnia alvei (H. alvei), and the potential types of quorum quenching enzymes by specific primer amplification. Four bacteria that showed significant degrading activity against the quorum sensing signals produced by H. alvei were isolated and identified as Enterobacter hormaechei (GS31), Bacillus cereus (GS44), Bacillus thuringiensis (GS48), and Serratia sp. (GS53). E. hormaechei GS31 exhibited the highest level of quenching activity, followed by Serratia sp. GS53, B. cereus GS44, and B. thuringiensis GS48. The cell-free supernatant of E. hormaechei GS31 and Serratia sp. GS53 contained compounds with potential quorum quenching activity, whereas the crude cell extract of B. cereus GS44 and B. thuringiensis GS48 contained such chemicals. The crystal violet staining and optical microscopy assay indicated that the isolated strains exhibited different inhibitory and dispersion capabilities against the biofilm of H. alvei. Among them, E. hormaechei GS31 exhibited the most significant effect, with inhibition and dispersion rates of 42.9% and 53.0%, respectively. The homologous gene amplification results suggested E. hormaechei GS31, B. cereus GS44, and Serratia sp. GS53 likely involved AiiA lactonase and PvdQ acylase gene. Additionally, B. thuringiensis GS48 was likely to possess AiiA lactonase gene. The screening and study of quorum quenching activity of strains degrading N-acyl homoserine lactone in soil enriching quorum quenching bacterial resources and provide a theoretical reference for developing aquaculture preservatives based on quorum quenching bacteria.